Bornyl Derivatives of p-(Benzyloxy)Phenylpropionic Acid: In Vivo Evaluation of Antidiabetic Activity - Sergey Kuranov; Olga Luzina; Mikhail Khvostov; Dmitriy Baev; Darya Kuznetsova; Nataliya Zhukova; Pavel Vassiliev; Andrey Kochetkov; Tatyana Tolstikova; Nariman Salakhutdinov (MDPI AG, 2020)
A series of bornyl derivatives of p-(benzyloxy)phenylpropionic acid were prepared, and their hypoglycemic activities were examined by an oral glucose tolerance test in mice. The results of this test revealed two compounds, 1 and 3, that can reduce the blood level of glucose similarly to reference compound vildagliptin. Both compounds were tested in an experiment on mice with metabolic disorders: the C57BL/6Ay strain. Along with hypoglycemic properties, the two compounds showed different abilities to correct lipid metabolism disorders. In silico prediction revealed that the studied substances are most likely bifunctional multitarget hypoglycemic compounds whose mechanism of action is based on a pronounced reduction in insulin resistance and a strong incretin-mimetic effect. The difference in the size of effects of these compounds on biochemical parameters of blood in the experiment on C57BL/6Ay mice was in good agreement with the computational prediction of the priority ranking of biological targets for these compounds. These results indicate that bornyl derivatives of p-(benzyloxy)phenylpropionic acid have a good potential as new agents for diabetes mellitus treatment due to their hypoglycemic and lipid-normalizing properties.